2015
DOI: 10.1016/j.cell.2015.11.015
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution CRISPR Screens Reveal Fitness Genes and Genotype-Specific Cancer Liabilities

Abstract: The ability to perturb genes in human cells is crucial for elucidating gene function and holds great potential for finding therapeutic targets for diseases such as cancer. To extend the catalog of human core and context-dependent fitness genes, we have developed a high-complexity second-generation genome-scale CRISPR-Cas9 gRNA library and applied it to fitness screens in five human cell lines. Using an improved Bayesian analytical approach, we consistently discover 5-fold more fitness genes than were previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

72
1,677
3
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,463 publications
(1,757 citation statements)
references
References 49 publications
72
1,677
3
5
Order By: Relevance
“…This number could grow dramatically via systematic complementation testing under different environments and genetic backgrounds. Moreover, complementation assays can also be carried out in other model systems including human cells (Hart et al , 2015). Based on only three large‐scale CRISPR studies (Wang et al , 2014; Blomen et al , 2015; Hart et al , 2015), cellular growth phenotypes (which might serve as the basis for an en masse selection) have already been observed in at least one cell line for 29% of human disease genes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This number could grow dramatically via systematic complementation testing under different environments and genetic backgrounds. Moreover, complementation assays can also be carried out in other model systems including human cells (Hart et al , 2015). Based on only three large‐scale CRISPR studies (Wang et al , 2014; Blomen et al , 2015; Hart et al , 2015), cellular growth phenotypes (which might serve as the basis for an en masse selection) have already been observed in at least one cell line for 29% of human disease genes.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, complementation assays can also be carried out in other model systems including human cells (Hart et al , 2015). Based on only three large‐scale CRISPR studies (Wang et al , 2014; Blomen et al , 2015; Hart et al , 2015), cellular growth phenotypes (which might serve as the basis for an en masse selection) have already been observed in at least one cell line for 29% of human disease genes. Beyond complementation, assays of protein interaction can, in addition to identifying variants directly impacting interaction, can detect variants ablating overall function through effects on protein folding or stability.…”
Section: Resultsmentioning
confidence: 99%
“…However, copynumber variation, including large duplications or deletions, can also profoundly influence health. The development of Cas9-mediated genome-wide gene knockout 75,76 and overexpression 77 screening highlights how multiplex assays could be used for understanding the effects of copy-number variation. These assays quantify the effect of single-gene deletion or overexpression.…”
Section: Limitations Of Maves and How To Overcome Themmentioning
confidence: 99%
“…In addition to their role in defining a "minimal gene set" (16,17), EGs tend to play important roles in protein interaction networks (18). Therefore, one may consider that EGs are involved in rate-limiting steps that affect a range of disease pathways (19).Recently, three large-scale screens (gene trap and CRISPRCas9) have been performed to assess the effect of single-gene mutations on cell viability or survival of haploid human cancer cell lines ("cell-based essentiality") (20)(21)(22). These studies identified an overlapping core set of genes that were essential in the majority of cell lines tested (n = 956), although a subset of genes were essential in specific cell lines.…”
mentioning
confidence: 99%